2021
DOI: 10.1111/jocd.14040
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of acne vulgaris and its clinico‐epidemiological pattern in adult patients: Results of a prospective, observational study

Abstract: Acne may continue from adolescent to adult age or newly develop in adults. Data also suggest rising prevalence of acne among post-adolescent patients. 4 Based on the age, patients with acne can be divided into three types: preadolescent, adolescent, and post-adolescent groups. [5][6][7] An extensive review involving 1,013 men and women reported acne among 50.9%, 35.2%, 26.3%, and 15.3% women in third decade, fourth decade, fifth decade of life, and beyond 50 years of age, respectively. 6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
5
9
0
Order By: Relevance
“…In our study, all the patients who used skincare products stated that they used them for the face, while the rates of those who used these products for the back and chest area were 7.1 and 5.8%, respectively. Similarly, in previous studies, a higher frequency of cosmetic product use was observed for the facial area, and there was a less cosmetic concern for the chest area 2,17 …”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In our study, all the patients who used skincare products stated that they used them for the face, while the rates of those who used these products for the back and chest area were 7.1 and 5.8%, respectively. Similarly, in previous studies, a higher frequency of cosmetic product use was observed for the facial area, and there was a less cosmetic concern for the chest area 2,17 …”
Section: Discussionsupporting
confidence: 63%
“…In studies in which AV patients were asked what worsened their disease, 14.3%‐58.2% stated that the use of cosmetics did 14,16‐18 . However, in these studies, make‐up products were also included as cosmetics.…”
Section: Discussionmentioning
confidence: 99%
“…A number of adult female patients with acne report worsening of their condition in the premenstrual period, as well as premenopausally, during pregnancy and during the use of progestin-only contraceptives. During these periods, women experience hormone fluctuations with a relative increase in the levels of those with androgenic activity (2,13,28). The reported incidence of these flare-ups slightly differs across studies.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…The association between acne and diet remains unclear. Studies have suggested that a Western diet, defined as high calorie intake, high glycemic load, high meat and fat intake, and high consumption of cow's milk and dairy products, may be associated with acne flares in predisposed individuals (13,28,30). This type of diet increases insulin and insulin-like growth factor 1 (IGF1) levels.…”
Section: Etiopathogenesismentioning
confidence: 99%
“…It is a common chronic inflammatory dermatosis that affects almost 85% of adolescents and young adults globally [4] . The prevalence of acne in adults is also rapidly increasing [5] . Reportedly, Acne vulgaris is affecting 2/3 rd of adults of age 18 and above [6] .…”
Section: Introductionmentioning
confidence: 99%